Dysregulated coagulation system links to inflammation in diabetic kidney disease - Xiao, Mengyun; Tang, Donge; Luan, Shaodong; Hu, Bo; Gong, Wenyu; Pommer, Wolfgang; Dai, Yong; Yin, Lianghong (Frontiers in Clinical Diabetes and Healthcare, 2023)
Diabetic kidney disease (DKD) is a significant contributor to end-stage renal disease worldwide. Despite extensive research, the exact mechanisms responsible for its development remain incompletely understood. Notably, patients with diabetes and impaired kidney function exhibit a hypercoagulable state characterized by elevated levels of coagulation molecules in their plasma. Recent studies propose that coagulation molecules such as thrombin, fibrinogen, and platelets are interconnected with the complement system, giving rise to an inflammatory response that potentially accelerates the progression of DKD. Remarkably, investigations have shown that inhibiting the coagulation system may protect the kidneys in various animal models and clinical trials, suggesting that these systems could serve as promising therapeutic targets for DKD. This review aims to shed light on the underlying connections between coagulation and complement systems and their involvement in the advancement of DKD.